Validity Test Using Principal Component Analysis (PCA) Involving Research Instruments on Learner-Centeredness, Knowledge-Centeredness, and Assessment-Centeredness - Nyak Mutia Ismail; Marisa Yoestara (International Conference on Multidisciplinary Research, 2022)
Instrument is an important element in research, including in educational research. In measuring learning environment formed in a teaching process, discrete variables need to be involved. Thence, understanding that teaching-learning process has varied pedagogical outcome(s), teachers and instructors can focus on their teaching orientation—learner-centeredness, knowledge-centeredness, or assessment-centeredness—and can avoid zoning-out of context during teaching with these factorial discrete variables. There are 15 factors determining the centeredness propensity in a research instrument developed based on Bransfrod et al. (2001). This study aims to simplify and reduce these factors to obtain dominant factors that influence the centeredness in a learning environment by using Principal Component Analysis (PCA). The study was conducted by collecting data through questionnaires to 10 respondents. Finally, 5 major factors were obtained. The main factor has an Eigenvalue of 3.95 with a variance of 26.38%. The second factor has an Eigenvalue of 3.51 with a variance of 23.43%. The third factor has an Eigenvalue of 2.46 with a variance of 16.44%. The fourth factor has an Eigenvalue of 1.95 with a variance of 12.99%. The fifth factor has an Eigenvalue of 1.10 with a variance of 7.37%. The overall factor gives a cumulative diversity proportion of 86.64%. Keywords: Construct validity, Assessment, Eigenvalue, and Principal Component Analysis.